2007
DOI: 10.1021/jp0657179
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Different Nanostructures of Cu2O (Nanothreads, Nanowires, and Nanocubes) by Simple Electrolysis Based Oxidation of Copper

Abstract: Cuprous oxide (Cu 2 O) nanostructures have been synthesized by anodic oxidation of copper through a simple electrolysis process employing plain water (with ionic conductivity ∼6 µS/m) as an electrolyte. No special electrolytes, chemicals, and surfactants are needed. The method is based on anodization pursuant to the simple electrolysis of water at different voltages. Platinum was taken as cathode and copper as anode. The applied voltage was varied from 2 to10 V. The optimum anodization time of about 1 h was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 40 publications
4
102
1
Order By: Relevance
“…The sequential dehydration of Cu(OH) 2 , as observed above in the thermal treatment process of as-prepared Cu(OH)2, must be responsible for the CuO formation. The electrochemical Cu2O formation on Cu foil was previous reported, 13,26 and could be understood by the following reaction:…”
Section: The Concentration Of Nucleophile Ohmentioning
confidence: 84%
“…The sequential dehydration of Cu(OH) 2 , as observed above in the thermal treatment process of as-prepared Cu(OH)2, must be responsible for the CuO formation. The electrochemical Cu2O formation on Cu foil was previous reported, 13,26 and could be understood by the following reaction:…”
Section: The Concentration Of Nucleophile Ohmentioning
confidence: 84%
“…It is well known that the surface energy of larger particles is lower than that of the smaller ones; therefore, these small nanoparticles were grown into larger ones via an overgrowth or aggregation process. [48][49][50][51] Afterwards, the adjacent large nanoparticles moved, met and then adhered to form a short chain-shaped structure (elongated nanorod structures). By prolonging the reaction time, the newly formed Co nanoparticle nuclei deposit onto the surface of the connected nanoparticles through the capillary phenomenon, leading to the formation of the nanowire morphology.…”
Section: Instrumentationmentioning
confidence: 99%
“…Single crystalline nanowires of hydroxides and oxides have been extensively studied. (Sharma & Sunkara, 2002;Singh et al, 2007) Their formations are related to the fact that the growth rate along one crystallographic direction is significantly faster than along the other directions. It has been reported that the growth direction of Gd(OH) 3 to nanorods is parallel to the (110) planes of the hexagonal unit cell.…”
Section: Synthesis Of High Quality Nanowires Of Gd 2 O 3 :Eu At Constmentioning
confidence: 99%